Effect of Snakehead Fish Albumin Extract Supplementation on SGOT and SGPT Levels in Tuberculosis Patients - Alfia Andriyani; Jusak Nugraha; Retno Indrawati; Theresia Budhy S; Nurul Hidayah; Mariana Asmaningdiah; Inas Hasna Azizah; Ahmad Hidayat (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Long-term use of OAT in tuberculosis patients carries a high risk of triggering drug-induced liver damage characterized by a spike in serum transaminase enzyme levels SGOT and SGPT. This study aims to determine the effect of snakehead fish extract therapy on SGOT and SGPT levels in TB patients undergoing intensive phase treatment. This study is quasi-experimental study with a randomized controlled trial design post-test only control group design. The research population was TB patients at the Sidotopo Community Health Center, Surabaya, who were selected using a random sampling technique purposive sampling until 20 respondents were obtained. Respondents were systematically divided into two groups, control group (OAT therapy) and treatment group (OAT therapy accompanied by supplementation of 500 mg albumin extract capsules). Comparative data analysis between groups was conducted using Independent Sample T-test. The results of the statistical analysis showed that the average SGOT level in intensive phase patients was 21.95 U/L and the average SGPT level was 19.65 U/L, where both valuesremained within normal clinical limits. The inter-group comparison hypothesis test produced a value p-value for SGOT levels of 0.907 and the value p-value for SGPT levels of 0.346. These data indicate no significant difference in the fluctuation of SGOT or SGPT levels between control and treatment groups. Supplementation with snakehead fish albumin extract did not show a significant difference in effect on SGOT and SGPT levels, but was proven to be able to maintain a stable and normal liver transaminase enzyme profile during intensive phase of OAT treatment.